Conformity in diversity? Isotopic investigations of infant feeding practices in two iron age populations from Southern Öland, Sweden - Howcroft, Rachel; Eriksson, Gunilla; Lidén, Kerstin (American journal of physical anthropology, 2012)
This article presents the results of a study of infant diet at two Iron Age sites on the island of Öland, Sweden. The cemetery at Bjärby contained a large number of subadults who had survived the earliest years of life, whereas most individuals at Triberga had died by 6 months of age. To investigate whether differences in infant feeding could explain the different mortality rates, the carbon, nitrogen, and sulfur stable isotope ratios of bone and tooth dentin collagen from the two sites were analyzed. Twenty‐two samples from Triberga and 102 from Bjärby yielded data that could be included in the carbon and nitrogen analysis. Twelve samples from Triberga and 42 from Bjärby were included in the sulfur analysis. The results for carbon (δ13C: Triberga X = –18.8, s.d. = 1.1; Bjärby X = –19.8, s.d. = 0.4), nitrogen (δ15N: Triberga X = 12.9, s.d. = 1.5; Bjärby X = 13.4, s.d. = 1.4), and sulfur (δ34S: Triberga X = 8.1, s.d. = 1.1; Bjärby X = 5.8, s.d. = 1.3) suggest that diet was broadly similar at both sites and based on terrestrial resources. At Bjärby, females and high‐status individuals consumed higher‐trophic level protein than other males from early childhood onward. There was some indication that the contribution of marine resources to the diet may also have differed between the sexes at Triberga. No consistent differences in breast milk intake were observed between the two sites, but there was substantial variation at each. This variation may reflect an influence of gender and social status on infant feeding decisions. Am J Phys Anthropol 149:217–230, 2012. © 2012 Wiley Periodicals, Inc.